2017
DOI: 10.1111/dme.13544
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and acute complications in children and young adults diagnosed with Type 1 diabetes in Yorkshire, UK: a cohort study

Abstract: Aims To examine all-cause and cause-specific mortality in a population-based cohort of people with early and late onset of Type 1 diabetes.Methods The Yorkshire Register of Diabetes in Children and Young People includes individuals with early (0-14 years) and late (15-29 years) Type 1 diabetes onset, diagnosed between 1978 and 2013. This register was linked to death certification data from the Office for National Statistics to calculate standardized mortality ratios, cumulative mortality curves using Kaplan-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…In this large population-based study, we observed < 6 deaths, consistent with another large population-based study that reported a low absolute mortality rate in early adulthood for individuals with childhood-onset diabetes [26]. Although the absolute mortality rate was relatively low, the risk of mortality in individuals with Type 1 diabetes is higher than in the general population and known to be related to acute diabetes complications [27][28][29]. We included all-causes of death because if the true cause of death was severe hypoglycaemia leading to a motor vehicle collision, for example, the cause of death may be documented as a motor vehicle collision and therefore not counted as a diabetesrelated death.…”
Section: Discussionsupporting
confidence: 89%
“…In this large population-based study, we observed < 6 deaths, consistent with another large population-based study that reported a low absolute mortality rate in early adulthood for individuals with childhood-onset diabetes [26]. Although the absolute mortality rate was relatively low, the risk of mortality in individuals with Type 1 diabetes is higher than in the general population and known to be related to acute diabetes complications [27][28][29]. We included all-causes of death because if the true cause of death was severe hypoglycaemia leading to a motor vehicle collision, for example, the cause of death may be documented as a motor vehicle collision and therefore not counted as a diabetesrelated death.…”
Section: Discussionsupporting
confidence: 89%
“…Population-based studies from Norway, Sweden and the UK report similar standardized mortality ratios from over a similar time period, ranging from 2.6 to 4.3 [21][22][23]. In the present study, it appears that even non-diabetes-related mortality in those with diabetes is higher than mortality in the control population.…”
Section: Discussionsupporting
confidence: 70%
“…A greater all-cause SMR was observed in studies conducted in Northern Ireland (SMR=2.96; 95% CI, 2.29-3.82) 31 , Brazil (SMR=3.13; 95% CI, 2.35-4.08) 32 , and Wales (SMR=2.91; 95% CI, 1.96-4.15) 25 . The all-cause SMR noted in our study (i.e., SMR=4.16) was comparable to the SMRs estimated from a Danish study (SMR=4.8; 95% CI, 3.5-6.2) 26 and a study conducted in Yorkshire, UK (SMR=4.3; 95% CI, 3.8-4.9) 13 . Disparity in all-cause SMR also existed within a country over time [5][6]27 .…”
Section: Overall and Cause-specific Analysissupporting
confidence: 84%
“…The recently improved mortality from type 1 diabetes is primarily due to enforced guidelines that emphasize tight glycemic control, blood pressure control, and treatment of dyslipidemia, as well as smoking cessation, in the management of type 1 diabetes [10][11][12] . Recent evidence suggests a reduction in mortality from chronic complications 8 but little change in mortality from acute complications of type 1 diabetes 13 . Mortality varies noticeably among countries 4 , and countries with a lower incidence of type 1 diabetes have higher absolute and relative mortality than higher incidence countries 6,14 .…”
Section: Introductionmentioning
confidence: 99%